Conservation and management of aquatic resources - Gautam, Ashutosh, 1965- (Delhi : Daya Pub. House, 1998)
With reference to India.
Includes bibliographical references and index.
Keywords: Aquatic ecology -- India; Water -- Pollution -- Environmental aspects -- India; Aquatic resources conservation -- India; Water quality management -- India